Redesenho das configurações estruturais na gestão universitária: ações derivadas da inovação e flexibilidade na legislação pós-LDB 1996 - Pinheiro, Helano Diógenes (2011)
This paper is set in a scenario in which higher education institutions suffer from external pressure to increase efficiency. The legislation after the Law of Directives and Bases for Education (LDBE), from 1996, is characterized by the fragmentation in its implementation, raising a concern with flexibility and innovation in several normative devices as well as aspects that must be incorporated to its organizational structure. The policies examined in this thesis are: Distance Education (DE); Law of Innovation and the Program of Support to Restructuring and Expansion of Federal Universities (PSREFU). This thesis aims to observe to what extent the characteristics of innovation and flexibility, which mark the new post- LDBE educational legislation, influence the organizational redesign of the Federal University of Ceará (UFC). For being about implementation policies, using contingency approach in order to collect the internal dynamics permeating the redesign of higher education institutions, the thesis focuses on the impacts caused by flexibility and innovation. This is a qualitative research, with case study methods, archive research and semi-structured interviews with members of the university administration. The results don t allow us to confirm the adoption of a more flexible and innovative configuration in the university but it is possible to identify the presence of those elements in the implementation changes, characterizing the hybrid structure. The changes mainly expose the extension of the management of projects to the administrative and academic components related to the institution. In terms of projection, the study found changes in the elements which characterize the current setting and the tendency of the university for adopting a diverse organizational structure. However, if the decentralization of management persists, the academic units may adopt their own structural solutions, but with no evidence of changes in the professional organization in most units. In this perspective, this thesis states that there are difficulties when incorporating innovation and flexibility to their organizational structure, which lead to improvised solutions, superposing skills through the redundancy of structures created with the same purpose or copying exogenous solutions